2016
DOI: 10.3390/nu8110687
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Red Meat/Refined Grain Diet and Dairy/Chicken/Nuts/Whole Grain Diet on Glucose, Insulin and Triglyceride in a Randomized Crossover Study

Abstract: Epidemiological studies suggest that a diet high in processed meat, with a high glycemic index is associated with an increased risk of type 2 diabetes. It is not clear if this is due to altered insulin sensitivity or an enhanced postprandial glucose. We aimed to compare the acute metabolic response of two different types of meals after ingestion of the matching diet for four weeks. The study was a randomized, crossover acute meal study. Volunteers consumed either a red meat/refined grain meal or a dairy/chicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 41 publications
3
33
0
2
Order By: Relevance
“…Fruits and vegetables have adequate antioxidant components, as well as supplying fibre and micronutrients . Dietary fibre in nuts, fruits and vegetables decreases the speed of gastric depletion and consequently, slowing glucose absorption . Low fat dairy intake is associated with increasing intracellular calcium that can lead to insulin secretion and improvement of glucose absorption .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fruits and vegetables have adequate antioxidant components, as well as supplying fibre and micronutrients . Dietary fibre in nuts, fruits and vegetables decreases the speed of gastric depletion and consequently, slowing glucose absorption . Low fat dairy intake is associated with increasing intracellular calcium that can lead to insulin secretion and improvement of glucose absorption .…”
Section: Discussionmentioning
confidence: 99%
“…26,27 The results of the Nurses' Health Study II (NHS II) and other observational studies that were mentioned above showed that adherence to these dietary patterns is associated with control of serum glucose and reduced risk of GDM and T2DM. 1,[26][27][28] The prudent dietary pattern with having fruits and root vegetables (source of antioxidants, dietary fibre, phytochemical and micronutrients such as magnesium and vitamin C), [29][30][31] nuts (source of dietary fibre, polyunsaturated fatty acid (PUFA) and micronutrients), [32][33][34][35][36] low-fat dairy (source of calcium, magnesium, whey protein and probiotic organism), 25,31,37,38 fish (source of omega 3 and vitamin D) 7,39,40 and poultry (source of proteins, PUFA and micronutrients) 36,41 can reduce the risk of GDM and T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Diets rich in red meat and refined grains have been shown to increase glucose and insulin response, which may increase pancreatic stress that could in turn increase the risk of type 2 diabetes. 17 The inclusion of eggs in the diets of our study participants did not show any meaningful change in the consumption of dairy products, while the exclusion of eggs in the diets led to a significant reduction. The effects of dairy products on type 2 diabetes are controversial.…”
Section: Discussionmentioning
confidence: 52%
“…More indirect support for the association between RMR and insulin comes from studies describing higher RMR in individuals with type 2 diabetes, contrasted with non-diabetics, which has been suggested, is due to insulin resistance [36]. Re ned grains had diminished insulin sensitivity, and one of the rst responses to alternations in insulin sensitivity is the change in hepatic insulin clearance rates [40]. The physiological mechanisms responsible for elevated RMR in individuals with insulin resistance are poorly understood.…”
Section: Discussionmentioning
confidence: 99%